Wolf 327b: a new member of the pack of ultra-short-period super-Earths around M dwarfs - Murgas, Felipe; Pallé, Enric; Orell-Miquel, Jaume; Carleo, I.; Peña-Moñino, L.; Pérez-Torres, M.; Watkins, C. N.; Jeffers, Sandra; Azzaro, M.; Barkaoui, K.; Belinski, A. A.; Caballero, José A.; et al. (Astronomy and astrophysics, 2024)
Planets with orbital periods shorter than 1 day are rare and have formation histories that are not completely understood. Small (Rp < 2 R⊕) ultra-short-period (USP) planets are highly irradiated, probably have rocky compositions with high bulk densities, and are often found in multi-planet systems. Additionally, USP planets found around small stars are excellent candidates for characterization using present-day instrumentation. Of the current full sample of approximately 5500 confirmed exoplanets, only 130 are USP planets and around 40 have mass and radius measurements. Wolf 327 (TOI-5747) is an M dwarf (R* = 0.406 ± 0.015 R⊙, M* = 0.405 ± 0.019 M⊙, Teff = 3542 ± 70 K, and V = 13 mag) located at a distance d = 28.5 pc. NASA’s planet hunter satellite, TESS, detected transits in this star with a period of 0.573 day (13.7 h) and with a transit depth of 818 ppm. Ground-based follow-up photometry, high resolution imaging, and radial velocity (RV) measurements taken with the CARMENES spectrograph confirm the presence of this new USP planet. Wolf 327b is a super-Earth with a radius of Rp = 1.24 ± 0.06 R⊕ and a mass of Mp = 2.53 ± 0.46 M⊕, yielding a bulk density of 7.24 ± 1.66 g cm−3 and thus suggesting a rocky composition. Owing to its close proximity to its host star (a = 0.01 au), Wolf 327b has an equilibrium temperature of 996 ± 22 K. This planet has a mass and radius similar to K2-229b, a planet with an inferred Mercury-like internal composition. Planet interior models suggest that Wolf 327b has a large iron core, a small rocky mantle, and a negligible (if any) H/He atmosphere.
Gesehen am 04.02.2025